2003
DOI: 10.1021/la0268505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nonionic Admixtures on the Adsorption of Ionic Surfactants at Fluid Interfaces. 2. Sodium Dodecylbenzene Sulfonate and Dodecylbenzene

Abstract: Equilibrium surface tension isotherms of sodium dodecylbenzene sulfonate (DDBS) are obtained at various fixed concentrations of NaCl. The contents of unsulfonated dodecylbenzene (DDB) in the used surfactant sample is determined by processing the surface-tension data. Having determined the parameters of the best fit, we computed the adsorption of surfactants (anionic DDBS and nonionic DDB), the binding of counterions in the Stern layer, the surface electric potential, the surface elasticity, etc., each of them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 19 publications
1
33
0
Order By: Relevance
“…As reported recently, DDBS is also very efficient in dispersing the nanotubes, but has considerable disadvantages: for example, DDBS is not available in pure form, and the impurities present are believed to be important to the detergent properties of DDBS [21] (similar effects have been observed for SDS [22] ). Also, the presence of an aromatic ring in this detergent limits its use in spectroscopic investigations.…”
Section: Resultsmentioning
confidence: 82%
“…As reported recently, DDBS is also very efficient in dispersing the nanotubes, but has considerable disadvantages: for example, DDBS is not available in pure form, and the impurities present are believed to be important to the detergent properties of DDBS [21] (similar effects have been observed for SDS [22] ). Also, the presence of an aromatic ring in this detergent limits its use in spectroscopic investigations.…”
Section: Resultsmentioning
confidence: 82%
“…The influence of the H + and OH − ions on the membrane tension can be also described by means of equations similar to Eq. (5.10), however, a multicomponent ionic adsorption should be considered, as in [59].…”
Section: Membrane Tensions: Results and Discussionmentioning
confidence: 99%
“…For the system under consideration, we can expect that the negatively charged ionizable groups on the two membrane surfaces serve as adsorption sites for positively charged cations (K + , Na + , etc.). To describe the counterion adsorption, we will employ the Stern model [54][55][56], which has been found to compare very well with the experiment [57][58][59].…”
Section: Adsorption Of Counterions At the Membrane Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Danov et al [25] had observed that pH had no influence on the CMC value in electrolytic solutions of NaCl at pH 2.5 and 6. In fact, one can conclude also that pH has no influence if the concentrations of sulfuric acid and sodium sulfate are similar.…”
Section: Determination Of Surfactant Cmc Valuementioning
confidence: 99%